Protective role of Dihydromyricetin in Alzheimer's disease rat model associated with activating AMPK/SIRT1 signaling pathway. Issue 1 (3rd January 2019) - Sun, Ping; Yin, Jun-Bo; Liu, Li-Hua; Guo, Jian; Wang, Sheng-Hai; Qu, Chun-Hui; Wang, Chun-Xia
Abstract : The aim of the present study was to understand the possible role of the Dihydromyricetin (DHM) in Alzheimer's disease (AD) rat model through regulation of the AMPK/SIRT1 signaling pathway. Rats were divided into Sham group, AD group, AD + DHM (100 mg/kg) group and AD + DHM (200 mg/kg) group. The spatial learning and memory abilities of rats were assessed by Morris Water Maze. Then, the inflammatory cytokines expressions were determined by radioimmunoassay while expressions of AMPK/SIRT1 pathway-related proteins by Western blot; and the apoptosis of hippocampal cells was detected by TdT-mediated dUTP nick end labeling assay. AD rats had an extended escape latency with decreases in the number of platform crossings, the target quadrant residence time, as well as swimming speed, and the inflammatory cytokines in serum and hippocampus were significantly elevated but AMPK/SIRT1 pathway-related proteins were reduced. Meanwhile, the apoptosis of hippocampal cells was significantly up-regulated with decreased Bcl-2 and increased Bax, as compared with Sham rats (all P <0.05). After AD rats treated with 100 or 200 mg/kg of DHM, the above effects were significantly reversed, resulting in a completely opposite tendency, and especially with 200 mg/kg DHM treatment, the improvement of AD rats was more obvious. DHM exerts protective role in AD via up-regulation of AMPK/SIRT1 pathway to inhibit inflammatory responses and hippocampal cell apoptosis and ameliorate cognitive function.